Functional Role of P-Glycoprotein and Binding Protein Effect on the Placental Transfer of Lopinavir/Ritonavir in the Ex Vivo Human Perfusion Model. (11th March 2009) - Ceccaldi, Pierre-Francois; Gavard, Laurent; Mandelbrot, Laurent; Rey, Elisabeth; Farinotti, Robert; Treluyer, Jean-Marc; Gil, Sophie
Abstract : Aims . To study the influence of P-glycoprotein (P-glycoprotein, ABCB1, MDR1) function on placental transfer of lopinavir with ritonavir at different albumin concentrations. Methods . Cotyledons were perfused with lopinavir, ritonavir, and the internal control antipyrin, at various albumin concentrations (10, 30, 40 g/L). After the control phase of each experiment, the P-glycoprotein inhibitor ciclosporin A was added at middle perfusion (45 minutes). Fetal Transfer Rate (FTR) and Clearance Index (CLI) were compared between the 2 phases. Results . In the control phase, the clearance index of lopinavir decreased from 0.401± 0.058 to 0.007± 0.027, as albumin concentrations increased from 10 g/L to higher concentrations (30, 40 g/L). When adding ciclosporin A at physiological albumin concentrations, the clearance index of lopinavir increased significantly 10.3 fold (95% of CI difference [− 0.156, − 0.002 ], P = .046 ) and became positive for ritonavir. Conclusions . Even at high albumin concentrations, inhibition of placental P-glycoprotein increased placental transfer of lopinavir, suggesting that this efflux pump actively reduces placental transfer of the drug. This mechanism may play a role in fetal exposure to maternal antiretroviral therapy.